The Relationship Between Public Knowledge and Behavior About Nutritional Status with the Incidence of Stunting in Boangmanalu Village - Suci Rahmadani Lingga; Reni Agustina Harahap (Universitas Ibn Khaldun Bogor, 2024)
Many growth and development problems occur in children, one of which is stunting. stunting is a condition where a person's height turns out to be shorter than the height of other people his age which is chronic during growth and development since the beginning of life.to find out the relationship between the level of knowledge and behavior of the community about nutritional status with the incidence of stunting in Boangmannalu Village. The type of research used in this study is Quantitative research with a cross-sectional design, the subjects in this study were mothers who had toddlers as many as 35 people. The results of this study showed that the incidence of stunting was 27 people (54.9%) who experienced a short, level of knowledge of parents who had toddlers, who had less knowledge about nutritional status as many as 17 people (55.6%), and most mothers who had less behavior about nutritional status as many as 17 people (55.6%). From the results of the study, it can be concluded that there is a relationship between the knowledge and behavior of mothers about the nutritional status of stunting toddlers in Boangmanalu Village, Pakpak Bharat Regency with p-value <0.005, which is 0.01 and 0.02 respectively.